Bare‐metal stent versus drug‐eluting stent in large coronary arteries. Issue 7 (26th February 2013) - Geng, Deng‐Feng; Meng, Zhe; Yan, Hai‐Yan; Nie, Ru‐Qiong; Deng, Jing; Wang, Jing‐Feng
<x xml:space="preserve">Abstract</x> Background Uncertainties exist with regard to the efficacy of drug‐eluting stent (DES) versus bare‐metal stent (BMS) in large coronary arteries. Objective and Methods The aim of this study was to investigate the efficacy of BMS versus DES in terms of clinical events in large coronary vessels (≥3.0 mm) by performing a meta‐analysis of all relevant randomized controlled trials (RCTs). Results Six RCTs with 4, 399 patients were included in this study. Overall, there were no significant between‐group differences in the risks of the composite of cardiac death and nonfatal myocardial infarction (cardiac death/MI), cardiac death, myocardial infarction, and stent thrombosis, however, DES was associated with significant reduction in the risk of target vessel revascularization (TVR) compared with BMS [0.48 (0.33, 0.70)] with consistent benefits among patients with reference vessel diameter ≥ 3.5 mm, reference vessel diameter ≥ 4.0 mm, stent length ≤ 15 mm, first‐generation DES or second‐generation DES. In patients with ≥ 3‐year follow‐up, there were no significant between‐group differences in the risk of cardiac death/MI, TVR, cardiac death, myocardial infarction or stent thrombosis. Conclusions This meta‐analysis suggests that DES is superior to BMS in terms of adverse cardiac events in large coronary arteries at the mid‐term follow‐up. The long‐term efficacy of newer‐generation DES versus BMS in larger coronary arteries is still worth further evaluation. © 2012 Wiley Periodicals, Inc.